Pemasaran Hijau dan Keputusan Pembelian: Peran Mediasi Citra Perusahaan - Hilmi, Matius Fauzi (Ekonomis: Journal of Economics and Business, 2025)
This study aims to test the effect of green marketing functions on corporate image. The research method used is purposive sampling to take samples by considering a criterion to be used as a sample. The test results found that there was a negative influence between green activities and corporate image. While the variables of green image and communication were proven to have a positive influence on corporate image.